The Discovery of the Rare Chara baueri (Charales, Charophyceae) in Serbia - Trbojević, Ivana (Plants (Basel), 2020)
Chara baueri is one of the rarest charophytes worldwide. It had been considered extinct in Europe for more than a century, from the 1870s to 2006, when it was rediscovered in Germany. The current distribution of this species is limited to a few localities in Europe (Germany, Poland and Russia), and one locality in Asia (Kazakhstan). We present a new finding of Chara baueri, to be a significant contribution to the species ecology and biogeography, and helping to review and update the current scarce knowledge. Chara baueri was discovered in Serbia and monitored for two vegetative seasons in 2018 and 2019, along with the associated macrophyte vegetation and water quality parameters. The morphology and ecology data of the species are presented comparatively with the literature data and the biogeography is critically reviewed. The population in Serbia is the first verified record of Chara baueri in southern Europe. Considering the recent findings and the knowledge accumulated in these records, Chara baueri was very possibly never extinct at all, but overlooked in Europe for the entire 20th century. We suggest that waterfowl migrating from the northern parts of Europe should be considered as the important spreading agent of Chara baueri in southern regions.